Effect of Feeding Intensity on Metabolic Maintenance, Reproduction and Welfare in Blue Fox (Vulpes lagopus) (Journal of Basic and Applied Research in Biomedicine, 2022)
The purpose was to evaluate effects of feeding intensity on metabolic maintenance, reproduction and welfare in blue fox vixens. Study groups were: Group 1: heavy slimming. Ad libitum feeding during September-November, aimed to produce extremely fat animals. Heavy slimming before breeding season, aim to have animals with normal breeding body condition. Group 2: maintenance of condition. Restricted feeding 35-45% from the level of Group 1 during September-November. Natural slimming to normal breeding condition. Group 3: Rising condition. Restricted feeding 50-60% from the level of Group 1 during September-November. Aim was to produce lean animals. Rising body condition was before breeding season, aimed to have animals with normal breeding body condition. Blood samples were taken regularly throughout the study. Results showed that urea concentration varied seasonally (P